Study on Callus Induction System of 4 Genotype of Napiergrass (Pennisetum purpureum ) - Umami, Nafiatul; Akashi, Ryo; Gondo, Takahiro; Ishigaki, Genki; Tanaka, Hidenori (ANIMAL PRODUCTION, 2016)
The aim of this study was to produce callus induction potential of 4 napiergrass (Pennisetum purpureum) genotypes (Dwarf Late, Hybrid, Merkeron and Wrukwona). Callus was induced from shoot apices of shoot tillersÂ  on MS media containing 2,4-D and BAP. On the MS medium containing 2 mg Lâ1 2,4-D and 0.5 mg Lâ1 BAP all genotypes could produce embryogenic calli, with different rate of growth. The best genotype for producing embryogenic calli was dwarf napiergrass in 60 day culture. These genotypes would be usefull for tissue cultured based research and for napiergrass improvement program, particularly in genetic transformation. Culturing shoot apices on MS medium containing 2 mgLâ1 2,4-D and 0.5 mgLâ1 BAP was more suitable than on MS medium containing 0.5 mgLâ1 2,4-D.Â  In the subculture with similar medium composition, proliferation occured poorly on dwarf napiergrass, whereas none happened on the three other genotypes. On the hormon-free medium, all genotypes germinated in different rates. This research pointed out that dwarf napiergrass gave the best response toward induction medium. However, its proliferation and regeneration needed to be optimized in order to obtain more obvious data. This genotype would be usefull for tissue culture based research and for napiergrass improvement program, particularly in genetic transformation.